EFFECT OF NET PROFIT MARGIN AND RETURN ON EQUITY ON THE STOCK PRICE - Delyana Rahmawany Pulungan; Muhammad Yalzamul Insan (International Journal of Economic, Technology and Social Sciences (Injects), 2020)
This research aims to know and analyze the influence of Net Profit Margin on the Share Price, to know and to know and analyze the influence of Return On Equity on the Share Price and to know and analyze the influence of Net Profit Margin and Return On Equity on the share price of Coal Mining Companies listed on the Indonesia Stock Exchange. This research approach uses a quantitative approach. The object of this research is the Coal Mining company listed on the Indonesia Stock Exchange (IDX) D from 2016 to 2019 which generates profit everys. The population used is 22 Coal Mining companies registered with IDX, the method of determining the number of samples used in this study is purposive sampling and selected as a sample of 8 companies. The results of this study show that partially Net Profit Margin has a negative and insignificant effect on the Share Price, and Return On Equity partially affects the Share Price. Simultaneously Net Profit Margin, Return On Assets, and Return On Equity affect the Share Price.